Functional characterization of FvCAMTA1in salt stress response of Fraxinus velutina - Yan, Liping; Geng, Dali; Wang, Yinhua; Sun, Chao; Li, Tianjiao; Wang, Baizhu; Yao, Junxiu; Ren, Fei; Yu, Lianjia (Frontiers in Plant Science, 2025)
The calmodulin-binding transcription activator (CAMTA) family plays crucial roles in calcium-mediated abiotic stress responses in plants. This study isolated and functionally characterized FvCAMTA1, a CAMTA gene from the salt-tolerant woody species Fraxinus velutina. Promoter analysis identified salt-responsive cis-elements, with a 157-bp core region sufficient for basal promoter activity and upstream sequences enhancing transcriptional activation under salt stress. FvCAMTA1 was predominantly expressed in leaves and rapidly induced by NaCl treatment. The heterologous overexpression of FvCAMTA1 in Arabidopsis significantly enhanced salt tolerance, resulting in higher germination rates, improved root elongation, and increased fresh weight, whereas the camta5 mutant exhibited heightened sensitivity. Yeast two-hybrid screening identified 46 proteins interacting with FvCAMTA1, including FvWRKY7 and FvPP2C60, interactions subsequently confirmed by bimolecular fluorescence complementation and luciferase complementation assays. Our findings demonstrate that FvCAMTA1 acts as a positive regulator in the salt stress adaptation of woody plants through calcium signaling and transcriptional networks, providing a valuable candidate gene for molecular breeding of stress-resistant trees.